Diagnostic utility of smartphone-integrated gait analysis in the assessment of BPPV - Durmus, Kasım; Bora, Adem; Sapci, Baris; Al-Hazzar, Marwan Khaled; Akti, Kerem; Kekul Sapci, Melek; Altuntas, Emine Elif (Frontiers in Neurology, 2025)
BackgroundBenign Paroxysmal Positional Vertigo (BPPV) is the most common vestibular disorder causing gait disturbances. Smartphone-based gait analysis has emerged as a portable, cost-effective alternative to laboratory-based assessments.ObjectiveTo evaluate the diagnostic utility of smartphone-based gait analysis in BPPV patients and its effectiveness in assessing treatment outcomes following canalith repositioning maneuvers.MethodsThis prospective case-control study included 26 patients with posterior canal BPPV and 37 demographically matched healthy controls. Gait analysis was performed using a smartphone application with participants walking 25 meters at a self-selected pace. In the BPPV group, measurements were repeated after Epley maneuver. Patient-reported outcomes were assessed using the Vertigo Symptom Scale (VSS), Vertigo Dizziness Imbalance Symptom Scale (VDI-SS), and Health Related Quality of Life (VDI -HRQoL).ResultsCompared to controls, BPPV patients demonstrated significantly fewer steps (31.31 ± 6.07 vs. 27.73 ± 6.52, p = 0.031), greater step length (0.54 ± 0.07 m vs. 0.63 ± 0.10 m, p < 0.001), and increased vertical center of mass displacement (1.59 ± 0.62 cm vs. 2.75 ± 0.95 cm, p < 0.001). Walking speed, cadence, and symmetry parameters showed no significant differences. Following canalith repositioning maneuvers, gait parameters remained unchanged, whereas patient-reported outcome scores improved significantly (VSS: p = 0.011, VDI-SS: p = 0.002, VDI -HRQoL: p = 0.038).ConclusionSmartphone-based gait analysis can identify characteristic gait abnormalities in BPPV patients, suggesting its potential as a complementary diagnostic tool. However, it appears less sensitive for detecting early post-treatment biomechanical changes despite symptomatic improvement. Further validation studies with larger samples and extended follow-up periods are warranted.